DEVELOPING ENGLISH LANGUAGE SKILLS THROUGH FAIRY TALES. - Xolmurodova, Olima (Журнал иностранных языков и лингвистики, 2021)
In this article, the authors highlighted the fairy tales as a medium in fostering language skills development. Fairy tales is used because it is considered suitable for all ages, besides, it also provides rich sources of language development, furthermore it has authentic model of language use. This study aims at proposing the use of fairy tales in developing language skills listening, speaking, reading and writing.